PENGEMBANGAN READING BOX UNTUK MENINGKATKAN MINAT BACA MAHASISWA - Sri Andreani Andreani; Utari Praba Astuti Astuti (Fakultas Sastra Universitas Negeri Malang, 2011)
Due to the unavailability materials for Reading II subject, this study attempts to develop a reading box material which consists of 80 units of 400-500 words. Each unit contains introduction, questions, readings, answer keys, reflection and also monitoring books. This reading box enables the students to practice reading extensively and independently. This material was developed through several stages, they were: planning, exploration, the development of the products, validation and laminating. In validation, the revision was done on the questions, readings, answer keys, reflections, illustration, lay out, the title and on the monitoring book. However, the results of the questionnaire on validation process show that the material was qualified in terms the content, the appropriateness of the reading type and its topic with the students’ interest and intellegence, the length of the readings, the variety of the text types, the difficulty level, illustration, lay out, the font and the letter size